2018
DOI: 10.1073/pnas.1806084115
|View full text |Cite
|
Sign up to set email alerts
|

Changes in resource partitioning between and within organs support growth adjustment to neighbor proximity in Brassicaceae seedlings

Abstract: SignificanceIn dense communities, plants compete for light and sense potentially threatening neighbors prior to actual shading. In response to neighbor proximity cues, shade-intolerant plants selectively elongate stem-like structures, thereby enhancing access to unfiltered sunlight. Although key steps in plant proximity sensing and signaling have been identified, we know little about the metabolic adaptations underlying enhanced stem growth. Here, we show that, following the detection of neighbor proximity cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 64 publications
2
49
0
Order By: Relevance
“…For picloram (Sigma-Aldrich, Steinheim, Germany, P5575) treatment, nylon meshes were transferred on day 5 before the temperature shift to half strength MS medium with the indicated picloram concentration (0.1% dimethyl sulphoxide (DMSO) for Mock). Seedlings imaging and measurements were described previously (de Wit et al, 2018). Petiole measurements were performed as described (de Wit et al, 2015).…”
Section: Phenotypic Characterization and Growth Conditionsmentioning
confidence: 99%
“…For picloram (Sigma-Aldrich, Steinheim, Germany, P5575) treatment, nylon meshes were transferred on day 5 before the temperature shift to half strength MS medium with the indicated picloram concentration (0.1% dimethyl sulphoxide (DMSO) for Mock). Seedlings imaging and measurements were described previously (de Wit et al, 2018). Petiole measurements were performed as described (de Wit et al, 2015).…”
Section: Phenotypic Characterization and Growth Conditionsmentioning
confidence: 99%
“…This suggests that carbon partitioning to starch vs sugars is altered in phyABD and phyABDE seedlings. A recent study analysing the starch biosynthesis mutants pgm1, pgi1, agd2, and the starch degradation mutant sex1 showed that seedling hypocotyl elongation negatively correlates with starch levels (de Wit et al, 2018). Mutants with the longest hypocotyls had the lowest starch levels, suggesting that sugars that are not partitioned to starch are used to grow.…”
Section: Discussion Phy Mutants Undergo a Developmental Switch In Metmentioning
confidence: 99%
“…Phytochromes are proposed to be involved in promoting root growth by cotyledon-derived sucrose (Kircher and Schopfer 2012). Work in Brassica seedlings illustrates that the proportion of assimilated carbon that is partitioned to the hypocotyl doubles in response to low R:FR conditions (de Wit et al 2018). This low R:FR induced change in carbon allocation is mainly dependent on PIF7, with contributions from PIF4 and / or PIF5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that barley is preferentially storing its resources in the youngest actively growing tissue where they are required for growth, and then store the excess in other tissues. Under shade by neighboring plants, Arabidopsis actively reallocates starch to the hypocotyls, likely to provide the C required for elongation (de Wit et al, 2018). Under LL, barley not only allocates starch or sucrose, but also malate to the youngest leaf.…”
Section: Light Intensity Affects the Spatial Distribution Of Metabolitesmentioning
confidence: 99%